The Use of Cohesive Devices in Academic Writing Written by English Language and Literature Department Students - Elvia Wilfitri; Sitti Fatimah (Universitas Negeri Padang, 2020)
This research was aimed to find out and analyse the type of Cohesive Devices used, and errors made by English Department Students at Universitas Negeri Padang in academic writing. This research was classified as descriptive qualitative research. The instruments used in this research were students’ writing task documents and tables. The documents were the students’ final academic writing products in the forms of mini theses focusing on the background of the problem. The data was taken by simple random sampling which resulting 25 academic writing product of English Department Student at Universitas Ngeri Padang of academic year 2017. The results in this research showed that the students use all types of the cohesive devices, but they only use a small amount of examples from each the types. Next, there are 102 transitions signals are used appropriately and 36 were used inappropriately. Then, 368 repetitions of key words or nouns are used appropriately and 25 are used inappropriately. The last 447 consistent pronouns are appropriately used and 115 are appropriately used.